The lack of attention as a secondary effect of inadequate penmanship pressure: Revelation of a phenomenological study (Revista Electrónica Calidad en la Educación Superior, 2025)
This article presents the results of a phenomenological study carried out with a group of 16 students with ASD 1, - who also had ADHD as a comorbid disorder and who, - to treat their attention deficit -, at the time of the research, they were receiving a pharmacological treatment that worked selectively. The purpose of the study was to demonstrate that there may be causes other than classic ADHD for the dispersed attention of a student with ASD1, due to which medication will not always produce the expected result. The results revealed a strong tendency of these students to reject activities related to writing, dramatically decreasing their concentration levels in the moments in which they had to write.
Keywords: attention; motivation; writing; grip of a pencil; dispersion; tiredness; fatigue; rejection